Antioxidant Activity of Purified Active Peptide Derived from Spirulina platensis Enzymatic Hydrolysates - Nur Maulida Safitri; Endang Yuli Herawati; Jue Liang Hsu (Research Journal of Life Science, 2017)
The aim of this study is to isolate the antioxidative peptide from Spirulina platensis. Peptide was obtained by proteolytic digestion, ultrafiltration, fractionation by RP-HPLC, identified by LC-MS/MS—MASCOT Distiller and measured its antioxidant activity by DPPH (2.2-Diphenyl-1-picrylhydrazyl) assay. Results showed that thermolysin was the most effective enzyme to digest this algae. The active peptide Phe-Ser-Glu-Ser-Ser-Ala-Pro-Glu-Gln-His-Tyr (m/z 1281.51) was identified and synthetized, which exhibited 45.98 ± 1.7% at concentration 128.15 µg/mL. Therefore, S. platensis is indicated as a potential therapeutic source for combating oxidative stress.